(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2016)
An investigation was conducted at Borjona village of Kapasia, Gazipur district during September 2011 to October 2012 to examine the biological performance of Indian spinach and papaya in litchi based agroforestry system. Papaya was planted between two litchi plants in each line and Indian spinach varieties were grown in the inter-space of two lines of litchi plant as well as control (farmers practice) in May 2012. Yield and yield contributing characters of Indian spinach varieties grown as litchi-papaya based agroforestry system and control did not vary. However, sprout plant-1 and sprout weight of Indian spinach varieties grown in litchi-papaya based system were significantly influenced while the other parameters did not vary. Sprout plant-1 of KS green (2.97) and local (2.89) variety were identical but higher over KS red variety (2.57). Sprout weight of KS red variety was the highest (85.80 g) while KS green and local variety gave lower and identical sprout weight. Though the yield did not vary among the varieties, KS red gave the highest yield (36.32 t ha- 1) followed by local (34.61 t ha-1) and KS green (34.00 t ha-1). In case of growth of litchi, plant height and stem diameter increment were 21.39 and 44.94 % over the eleven months observation period. The yield of papaya was quite satisfactory with an average 42 fruits per plant with 23.71 t ha-1. Therefore, in the Litchi-Papaya-Indian spinach based system, Indian spinach varieties could be ranked as KS red > Local> KS green. Int. J. Agril. Res. Innov. & Tech. 6 (1): 34-40, June, 2016